When Courts Speak: Substantive Justice for Disabilities in CASN Recruitment on Trial - Rizki, Muhammad; Nurikah, Nurikah; Jazuli, H.E Rakhmat; Rayhan, Ahmad (JURNAL LEGALITAS, 2025)
The statutory 2% labour quota for persons with disabilities, as mandated by Law No. 8 of 2016, remains largely unfulfilled. Discriminatory practices persist in the recruitment of civil servants, as illustrated by the case of Muhammad Baihaqi (Supreme Court Decision No. 471 K/TUN/2021). This study aims to analyse the capacity of the State Administrative Court (PTUN) to deliver substantive justice and to identify the key obstacles that hinder such efforts. The methodology employed is a doctrinal legal study, utilising primary legal sources (statutes and court decisions) and secondary materials (reports from the Central Statistics Agency [BPS], academic literature, journal articles, and media coverage). Findings indicate that lower administrative courts tend to prioritise procedural compliance, such as adherence to filing deadlines, while neglecting the substantive issue of discrimination. In contrast, the Supreme Court underscored the importance of substantive justice; however, systemic barriers remain prevalent. For instance, in 2019, only 0.017% of civil servant hires were persons with disabilities, reflecting ongoing institutional bias and inadequate reasonable accommodation. This study is the first to explicitly link the procedural rigidity of PTUN to broader human rights violations, arguing for a paradigm shift towards a socio-legal approach that bridges administrative law with justice for persons with disabilities. The paper recommends several reforms: stricter enforcement of the labour quota, the standardisation of disability-inclusive recruitment assessments, the imposition of sanctions for non-compliance, and the integration of disability rights training for judges. Urgent institutional reforms are necessary to align administrative law with human rights principles and to ensure equitable participation of marginalised groups in public employment.